Adrenergic regulation of cytoplasmic structures related to secretory processes in pig pinealocytes—an ultrastructural, quantitative study. (October 2017) - Przybylska-Gornowicz, Barbara; Lewczuk, Bogdan; Ziółkowska, Natalia; Prusik, Magdalena
Highlights: Membrane-bounded bodies, dense core vesicles and the Golgi apparatus are under adrenergic control in pig pinealocytes. Adrenergic stimulation increases the numerical density of the DCV and decreases the relative volumes of the Golgi apparatus and MBB Norepinephrine controls the dense core vesicles and the Golgi apparatus via beta-adrenoceptors. Membrane-bounded bodies are controlled via the beta- and alpha1-adrenoceptors. Abstract: Two structures, considered as secretory in nature, are present in the pinealocytes in of the domestic pig show the presence of two structures, which are considered as secretory in nature – the dense core vesicles (DCV) and the membrane bounded (dense) bodies (MBB). The latter are extremely numerous in pig pinealocytes (they occupy 6–20% of the cytoplasm), and the number of MBB changes under different physiological and experimental conditions. Norepinephrine is the main neurotransmitter that regulates the secretion of pineal melatonin. The present study was carried out to 1) clarify whether the DCV and their source – the Golgi apparatus (GA) – as well as the MBB are controlled by norepinephrine, 2) determine the effect of adrenergic stimulation on these structures, and 3) identify the receptors involved in the regulation of these structures. The studies were performed using a static organ culture of pig pineal explants. The explants were incubated in a control medium between 08:00 and 20:00 and in a medium with 10 μM norepinephrine or alpha- or beta-adrenoceptor agonists between 20:00 and 08:00 on five consecutive days. The tissues were subsequently prepared for ultrastructural analysis. The results distinctly showed that the DCV, GA and MBB in pig pinealocytes are under adrenergic control. The stimulation of the beta-adrenoceptors resulted in an increase in the numerical density of the DCV and a decrease in the relative volume of the GA in the perikarya, while the incubation with agonists of the alpha1-adrenoceptors was ineffective. The relative volume of the MBB in the perikarya significantly decreased after treatment with both beta-agonists and alpha1-agonists, which suggested the involvement of two types of adrenoceptors in the regulation of these structures.